Afiksasi pada Bahasa Jawa, Bahasa Inggris, dan Bahasa Indonesia - Ja’a Nazielatu Rois Nabilla; Fitri Anekawati (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study aims to analyze the process of affixation, which is the addition of elements to the basic form of a word, in three languages: Indonesian, English, and Javanese. Affixation is one of the important morphological processes in the formation of words that reflects the structure and characteristics of each language. This study uses a descriptive qualitative approach by utilizing speech from the three languages as comparative data. Data was collected through the listening method, which is by observing the use of language in various contexts, both oral and written, including excerpts from texts that contain language errors. The analysis was carried out on the basic forms of words that undergo the process of affixation, focusing on four types of affixes: prefixes (prefixes), infixes (inserts), suffixes (suffixes), and confixes (a combination of prefixes and suffixes). The results show that the three languages have a distinctive affixation pattern, although there are some similarities in the function and purpose of word formation. Indonesian and Javanese tend to have a more complex and productive attribution structure than English, which is more dominant in using suffixes in the formation of new words. This study also found that language errors in writing are often related to the use of affixes that are not in accordance with the morphological rules of each language. These findings show the importance of understanding the process of affixation in language learning and language competence development. By understanding the differences and similarities in the process of interlingual affixation, it is hoped that language learners and practitioners can improve the accuracy of word use and enrich cross-cultural linguistic insights.